Pemenuhan Hak Dan Kewajiban Suami Isti Penyandang Ketebelakangan Mental Perspektif Maqasid Syariah - asna, lidia; haqiqi amirullah, luqman (Al-Hukkam: Journal of Islamic Family Law, 2025)
The occurrence of marriage of course cannot be separated from the relationship between the rights and obligations of husband and wife, as well as marriages between people with mental retardation, they must fulfill their obligations as husband and wife like couples in general, but in fact, mentally retarded couples in Sembung Village, Banyuputih District, Batang Regency have difficulty fulfilling their rights. and their obligations as husband and wife. This research is a type of field research using a qualitative approach. The results of the research show that people with mental retardation cannot fulfill their obligations independently, they have to use the help of other people, they cannot fulfill several rights and obligations of husband and wife, husband and wife who both have mental retardation cause a lot of harm (badness) for both them and their home life. Overall, fulfilling the rights and obligations of people with mental retardation is not in line with fulfilling the objectives of Islamic law in maintaining all aspects of maslahah in maqasid sharia, namely hifz ad-din, hifz al-aql, hifz an-nafs, hifz al-nasl, hifz al- mall